Fabrication and conduction mechanism evaluation of polyfluorene polymeric Schottky diode†. (13th May 2015) - Mustafa, Maria; Sherin, Lubna; Kim, Hyung Chan; Lee, Yun Woo; Choi, Kyung Hyun
<x xml:space="preserve">Abstract</x> A thin film of polyflourene polymer was sandwiched between a conductive polymer deposited on silver nanowire and metal electrode to form a multilayer polymer‐based diode device. The electrical properties of fabricated polymeric diode have been studied by current–voltage method. The current–voltage characteristics of the fabricated device exhibited non‐ideal, asymmetrical, and rectifying behavior. Ohmic current conduction mechanism was observed in the device at low voltage. At higher voltage values, the space‐charge‐limited current conduction mechanism was found to be dominated. The values of the Schottky barrier height, ideality factor, and saturation current density were extracted according to the standard thermionic emission model and discussed. The barrier height and ideality factor were calculated as 0.72 eV and 2.53, respectively. Copyright © 2015 John Wiley & Sons, Ltd.